Gender Perspective in the National Reform Programme for Employment - Zamfir, Elena (Calitatea Vieții, 2010)
This paper explores the recent changes in Romanian employment policy, with particular regard to the situation of women. During 2008, we observed some changes in Romania employment policy, but no clearly visible gender equality. It was immediately noticeable that many produced changes in different social domains were not oriented explicitly towards increasing equal opportunities between men and women. The economic crisis, doubled by the financial and social crises, has brought many additional threats to women in Romanian Society. These relate to them losing their jobs, being victims of poverty and social exclusion, increasing their economic and financial dependence on men and their gradual loss of autonomy, dramatically decreasing their participation at the highest level of political and professional decision making. Moreover, the improvements for women in the field of flexicurity which had appeared over time in Romania under the general Lisbon strategy developments, despite the many barriers and difficulties to overcome, are now in danger of being lost due to a new incoherent crisis policy of jobs protection and new legislation set up quickly, under pressure, as the crisis deepened.